Advancement in Vascularized Toe PIP Joint Transfers: Technical Evolution and Current Practices - Lee, Che-Hsiung; Lin, Yu-Te (Seminars in Plastic Surgery, 2025)
Vascularized toe proximal interphalangeal joint transfer has evolved as a biological solution for posttraumatic finger joint reconstruction. Extension lag has been recognized as a major challenge since its introduction in the 1980s. A significant advancement came from the 2013 anatomical study that characterized two distinct patterns of toe extensor mechanism: Type 1 (>95%) lacking obvious central slip insertion, and Type 2 (<5%) with clear central slip insertion. This understanding led to customized reconstruction strategies based on both donor toe anatomy and recipient finger condition. Various techniques, including centralization, direct repair, and central slip reconstruction, have been developed. The Te technique was developed to minimize bone manipulation while achieving similar functional outcomes to the traditional Stack technique. Current evidence demonstrates that proper execution of central slip reconstruction can achieve consistent functional results regardless of the technique chosen.
Keywords: vascularized toe joint transfer; proximal interphalangeal joint; central slip reconstruction; extensor mechanism reconstruction; finger joint reconstruction